Between a rock and a hard place: adaptive sensing and site‐specific dispersal. (30th June 2020) - Nichols, Bethany S.; Leubner‐Metzger, Gerhard; Jansen, Vincent A. A.
Abstract: Environmental variability can lead to dispersal: why stay put if it is better elsewhere? Without clues about local conditions, the optimal strategy is often to disperse a set fraction of offspring. Many habitats contain environmentally differing sub‐habitats. Is it adaptive for individuals to sense in which sub‐habitat they find themselves, using environmental clues, and respond plastically by altering the dispersal rates? This appears to be done by some plants which produce dimorphic seeds with differential dispersal properties in response to ambient temperature. Here we develop a mathematical model to show, that in highly variable environments, not only does sensing promote plasticity of dispersal morph ratio, individuals who can sense their sub‐habitat and respond in this way have an adaptive advantage over those who cannot. With a rise in environmental variability due to climate change, our understanding of how natural populations persist and respond to changes has become crucially important. Abstract : Environmental variability can lead to dispersal: why stay put if it is better elsewhere? Here we develop a mathematical model to show, that in highly variable environments, not only does sensing promote plasticity of dispersal morph ratio, but individuals who can sense their sub‐habitat and respond in this way have an adaptive advantage over those who cannot. With a rise in environmental variability due to climate change, our understanding of how natural populations persist and respond to changes has become crucially important.